Loss of the ORF in the SSUrDNA group I intron of one Naegleria lineage. - De Jonckheere, J F (1994)
We have found a Naegleria lineage in which the SSUrDNA contains a group I intron with a length of 375 nucleotides. This is a unique finding because all group I introns detected until now in Naegleria are 1.3 kilobases long and contain an open reading frame coding for 245 amino acids. Sequence data show that the 375 nucleotide-long intron is at the same place in the SSUrDNA as, and is descendant from, the 1.3 kilobase group I intron present in other species of Naegleria. Our data indicate that in one lineage of Naegleria the group I intron lost part of its DNA that is not contributing to the secondary structure but that carries the open reading frame. The amoeboflagellate genus Naegleria contains strains without the intron and strains with the intron, with or without an open reading frame. Therefore, this genus provides a unique opportunity to study the function and evolution of both the group I intron and the open reading frame.